[Volcanoes on Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of the volcanoes on Heimaey. The two, dark formations sit on the grassy, flat island lined with brown rock. The volcano to the left is dusted with white throughout. Rectangular buildings sit in the close cluster to the right, ahead of the second volcano. White birds sit along the rocky edge of the island and along rock peeking out of the grey water in the foreground.